Inter- and Intrareader Agreement of NI-RADS in the Interpretation of Surveillance Contrast-Enhanced CT after Treatment of Oral Cavity and Oropharyngeal Squamous Cell Carcinoma - Elsholtz, F.H.J.; Ro, S.-R.; Shnayien, S.; Erxleben, C.; Bauknecht, H.-C.; Lenk, J.; Schaafs, L.-A.; Hamm, B.; Niehues, S.M. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: The Neck Imaging Reporting and Data System was introduced to assess the probability of recurrence in surveillance imaging after treatment of head and neck cancer. This study investigated inter- and intrareader agreement in interpreting contrast-enhanced CT after treatment of oral cavity and oropharyngeal squamous cell carcinoma.MATERIALS AND METHODS: This retrospective study analyzed CT datasets of 101 patients. Four radiologists provided the Neck Imaging Reporting and Data System reports for the primary site and neck (cervical lymph nodes). The Kendall's coefficient of concordance (W), Fleiss κ (κF), the Kendall's rank correlation coefficient (τB), and weighted κ statistics (κw) were calculated to assess inter- and intrareader agreement.RESULTS: Overall, interreader agreement was strong or moderate for both the primary site (W = 0.74, κF = 0.48) and the neck (W = 0.80, κF = 0.50), depending on the statistics applied. Interreader agreement was higher in patients with proved recurrence at the primary site (W = 0.96 versus 0.56, κF = 0.65 versus 0.30) or in the neck (W = 0.78 versus 0.56, κF = 0.41 versus 0.29). Intrareader agreement was moderate to strong or almost perfect at the primary site (range τB = 0.67–0.82, κw = 0.85–0.96) and strong or almost perfect in the neck (range τB = 0.76–0.86, κw = 0.89–0.95).CONCLUSIONS: The Neck Imaging Reporting and Data System used for surveillance contrast-enhanced CT after treatment of oral cavity and oropharyngeal squamous cell carcinoma provide acceptable score reproducibility with limitations in patients with posttherapeutic changes but no cancer recurrence.BIBreast ImagingCECTcontrast-enhanced CTLILiver ImagingNINeck ImagingOCSCCoral cavity squamous cell carcinomaOPSCCoropharyngeal squamous cell carcinomaPIProstate ImagingRADSReporting and Data System